Field Application of Automated Spectrophotometric Analyzer for High-Resolution In Situ Monitoring of pH in Dynamic Estuarine and Coastal Waters - Nehir, Münevver; Esposito, Mario; Loucaides, Socratis; Achterberg, Eric P. (Frontiers in Marine Science, 2022)
High quality pH measurements are required in estuarine and coastal waters to assess the impacts of anthropogenic atmospheric CO2 emissions on the marine carbonate system, including the resulting decrease in pH. In addition, pH measurements are needed to determine impacts on carbonate chemistry of phytoplankton blooms and their breakdown, following enhanced anthropogenic nutrient inputs. The spectrophotometric pH technique provides high quality pH data in seawater, and is advantageous for long-term deployments as it is not prone to drift and does not require in situ calibration. In this study, a field application of a fully automated submersible spectrophotometric analyzer for high-resolution in situ pH measurements in dynamic estuarine and coastal waters is presented. A Lab-on-Chip (LOC) pH sensor was deployed from a pontoon in the inner Kiel Fjord, southwestern Baltic Sea, for a total period of 6 weeks. We present a time-series of in situ pHT (total pH scale) and ancillary data, with sensor validation using discretely collected samples for pHT and laboratory analysis. The mean difference between the sensor and laboratory analyses of discrete samples was within ±0.015 pHT unit, with a mean of 0.001 (n=65), demonstrating that the LOC sensor can provide stable and accurate pHT measurements over several weeks.